Leaders and Followers Algorithm for the Binary Knapsack Problem - Angmalisang, Helen Yuliana; Angmalisang, Harrychoon; Anggriani, Nita (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2025)
The Leaders and Followers (LaF) algorithm, as a relatively recent metaheuristic compared to other well-established algorithms, has demonstrated strong performance in solving continuous constrained optimization problems, the balanced transportation problem, and the traveling salesman problem. The distinctive feature of the LaF algorithm lies in its dual-population structure, where two groups operate with different roles, namely exploration and exploitation, to balance search diversity and convergence. This design effectively prevents premature convergence. In this study, the LaF algorithm is applied to address the binary knapsack problem. The proposed algorithm was evaluated using a well-established benchmark dataset for this problem. The results indicate that the LaF algorithm exhibits stable performance in solving binary knapsack problems with moderately sized capacities and outperforms several other metaheuristic algorithms